Charge trapping by self-assembled monolayers as the origin of the threshold voltage shift in organic field-effect transistors - Gholamrezaie, Fatemeh; Andringa, Anne-Marije; Roelofs, W. S. Christian; Neuhold, Alfred; Kemerink, Martijn; Blom, P. W. M.; Leeuw, Dago M. de (Small, 2012)
The threshold voltage is an important property of organic field-effect transistors. By applying a self-assembled monolayer (SAM) on the gate dielectric, the value can be tuned. After electrical characterization, the semiconductor is delaminated. The surface potentials of the revealed SAM perfectly agree with the threshold voltages, which demonstrate that the shift is not due to the dipolar contribution, but due to charge trapping by the SAM.